Bhutan journal of animal science - Department of livestock (Thimphu : Department of livestock, 2017)
Coinciding with the start of 12th FYP, DoL has formally released Bhutan Journal of Animal Science (BJAS), Vol. 2, Issue 1, 2018, as a tribute to researchers from within and outside Bhutan and to acknowledge their contributions to animal science. This volume also has a paper from an Animal Breeder from Nepal Animal Science Research Institute (NASRI) under Nepal Agriculture Research Council (NARC). The Department of Livestock (DoL) is sharing journal copies with international agencies and institutes of SAARC countries.